Young Infants Match Facial and Vocal Emotional Expressions of Other Infants. (25th March 2013) - Vaillant‐Molina, Mariana; Bahrick, Lorraine E.; Flom, Ross
Abstract : Research has demonstrated that infants recognize emotional expressions of adults in the first half year of life. We extended this research to a new domain, infant perception of the expressions of other infants. In an intermodal matching procedure, 3.5‐ and 5‐month‐old infants heard a series of infant vocal expressions (positive and negative affect) along with side‐by‐side dynamic videos in which one infant conveyed positive facial affect and another infant conveyed negative facial affect. Results demonstrated that 5‐month‐olds matched the vocal expressions with the affectively congruent facial expressions, whereas 3.5‐month‐olds showed no evidence of matching. These findings indicate that by 5 months of age, infants detect, discriminate, and match the facial and vocal affective displays of other infants. Further, because the facial and vocal expressions were portrayed by different infants and shared no face–voice synchrony, temporal, or intensity patterning, matching was likely based on detection of a more general affective valence common to the face and voice.